A non-integrated type noise suppressor incorporated with a highly resistive Co-Fe-Al-O thin film on a coplanar waveguide transmission line - Sohn, Jaecheon; Han, S. H.; Kim, Ki Hyeon; Yamaguchi, Masahiro; Lim, S. H. (ELSEVIER SCIENCE BV, 2007)
A non-integrated type noise suppressor on a coplanar waveguide (CPW) transmission line is demonstrated by using a highly resistive Co41Fe38Al13O8 (in atomic %) nanogranular thin film with the dimensions of 4 mm (l) x 4 mm (w) x 0.1 mu m (t). Due to high resistivity of the magnetic thin film, no insulating layer is disposed between the CPW line and the film. The insertion loss is very low being less than 0.3 dB and this low value is maintained up to 2 GHz. At a ferromagnetic resonance frequency of 3.3 GHz where a large power loss is observed, the degree of noise attenuation is increased significantly reaching 2dB. This level of noise attenuation is still small for real applications, but, considering a small magnetic volume used in this work, further improvement is expected by simply increasing the magnetic volume and also integrating the magnetic thin film into the CPW transmission line. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: MAGNETOELASTIC DEVICE APPLICATIONS; HIGH ELECTRICAL-RESISTIVITY; PERMEABILITY